Optimal economic dispatching strategy for power systems considering distributed controllable load clusters - Zhang, Chunmei; Jiang, Jiang; Cai, Chunyuan; Yu, Hengyou; Yang, Duotong; Li, Zhuohuan (Frontiers in Energy Research, 2024)
The day-ahead dispatching of power system depends on the predicted renewable energy output and load power, which brings great challenges to the real-time power balance. This paper focuses on voltage sensitive loads (VSLs) that are widely distributed in space, thus exploring the real-time dispatching potential for VSLs. Firstly, based on the P-V relationship of VSLs clusters, a ZIP model is adopted to establish VSLs’ power controllable model. Meanwhile, considering the potential voltage instability risk during the process of voltage regulation, a linear relationship between voltage safety margin (VSM) index and node power variation was derived. Then, a two-stage linear dispatching model for controllable VSLs clusters was established to meet the needs of online application. In detail, the first stage mainly focuses on evaluating the scheduling potential of VSLs clusters and the second stage determines the optimal real-time response strategy for VSLs clusters. Finally, the effectiveness and feasibility of the proposed method are verified through an improved IEEE-30 node system.